The Politics of Children's Rights and Representation - Sandin, Bengt; Josefsson, Jonathan; Hanson, Karl; Balagopalan, Sarada (Studies in Childhood and Youth,, 2023)
This edited volume investigates children and youth's deep entanglement in today's major global, national, and local transformations and processes: wherein they are not mere spectators and objects of transformations but instead actively shape them through various social, economic, and political representations. International contributions illuminate the problems that arise when children's rights and participation become a site of contestation and power over who represents whom, what, when, and where. The authors do not provide simple solutions, instead offering an understanding of the fundamental nature of these problems as founded in the application of rights and the nature of representation in modern society. Together, the authors emphasize that child representation must take into account the local and spatial context of how representations of children are discussed, as well as possible discrepancies between local, regional, national, and global processes. Bengt Sandin is Professor Emeritus of Child Studies in the Department of Thematic Studies at Linköping University, Sweden. His previous publications include Schooling and State Formation in Early Modern Sweden (2020). Jonathan Josefsson is Assistant Professor of Child Studies in the Department of Thematic Studies at Linköping University, Sweden. His previous publications include Children at the Borders (2016) and Empowered Inclusion: Theorizing Global Justice for Children and Youth (2020). Karl Hanson is Professor of Public Law and Director of the Centre for Children's Rights Studies at the University of Geneva, Switzerland. His previous publications include Reconceptualizing Children's Rights In International Development: Living Rights, Social Justice, Translations (2013). He is an editor of Childhood. Sarada Balagopalan is Associate Professor of Childhood Studies at Rutgers University-Camden, USA. Her previous publications include Inhabiting 'Childhood': Children, Labour and Schooling in Postcolonial India (2014). .